2020
DOI: 10.1055/s-0040-1712495
|View full text |Cite
|
Sign up to set email alerts
|

Análise da inclinação tibial posterior como fator de risco para lesão do ligamento cruzado anterior

Abstract: Resumo Objetivo O objetivo do presente estudo foi avaliar a relação entre pacientes com lesão do ligamento cruzado anterior (LCA) por trauma indireto e o aumento da inclinação posterior da tíbia. Métodos Estudo retrospectivo, realizado por análise de prontuários e radiografias digitais de pacientes, presentes em banco de dados de um hospital terciário de ortopedia e traumatologia. A amostra foi composta por dois grupos, sendo o primeiro formado por pacientes com diagnóstico de lesão do LCA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, another study found a statistically significant association only between lateral PTS and ACL injuries, not medial PTS [ 12 ]. Additionally, one study suggested that individuals with a PTS above 8° were at an increased risk of ACL injury [ 13 ]. Notably, while ACL injury has been associated with lateral posterior tibial inclination, a meta-analysis suggests that both medial and lateral posterior tibial inclination are linked to ACL injuries [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study found a statistically significant association only between lateral PTS and ACL injuries, not medial PTS [ 12 ]. Additionally, one study suggested that individuals with a PTS above 8° were at an increased risk of ACL injury [ 13 ]. Notably, while ACL injury has been associated with lateral posterior tibial inclination, a meta-analysis suggests that both medial and lateral posterior tibial inclination are linked to ACL injuries [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%